Indian hedgehog signaling and the role of graft tension in tendon‐to‐bone healing: Evaluation in a rat ACL reconstruction model. Issue 4 (25th November 2015) - Carbone, Andrew; Carballo, Camila; Ma, Richard; Wang, Hongsheng; Deng, Xianghua; Dahia, Chitra; Rodeo, Scott
ABSTRACT: The structure and composition of the native enthesis is not recapitulated following tendon‐to‐bone repair. Indian Hedgehog (IHH) signaling has recently been shown to be important in enthesis development in a mouse model but no studies have evaluated IHH signaling in a healing model. Fourteen adult male rats underwent ACL reconstruction using a flexor tendon graft. Rats were assigned to two groups based on whether or not they received 0N or 10N of pre‐tension of the graft. Specimens were evaluated at 3 and 6 weeks post‐operatively using immunohistochemistry for three different protein markers of IHH signaling. Quantitative analysis of staining area and intensity using custom software demonstrated that IHH signaling was active in interface tissue formed at the healing tendon‐bone interface. We also found increased staining area and intensity of IHH signaling proteins at 3 weeks in animals that received a pre‐tensioned tendon graft. No significant differences were seen between the 3‐week and 6‐week time points. Our data suggests that the IHH signaling pathway is active during the tendon‐bone healing process and appears to be mechanosensitive, as pre‐tensioning of the graft at the time of surgery resulted in increased IHH signaling at three weeks. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:641–649, 2016.